2019
DOI: 10.1111/sms.13384
|View full text |Cite
|
Sign up to set email alerts
|

The team effect on doping in professional male road cycling (2005‐2016)

Abstract: This article questions organizations’ (clubs, teams, etc) responsibility in doping use from the case of anti‐doping rules violations (ADRVs) sanctioned by the Union Cycliste Internationale in professional cycling. We built a database with 271 caught riders among 10 551 professional riders employed from 2005 to 2016 in the three first world divisions. We developed a time‐discrete event history model with a multilevel perspective to consider if the ADRV is related to the characteristic of a rider's career path (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies placed in SRP employed four different methods for determining prevalence, which were Direct Survey (DS) , Random Response Technique (RT) [102][103][104][105][106][107][108][109][110], Qualitative Interviews (QI) [111], and Network Scale Up (NS) [55]. Studies placed in SAP employed four different methods for determining prevalence, which were Testing Figures (TF) [112][113][114][115][116][117][118][119][120][121], Blood Profile (BP) [122][123][124], Anti-Doping Rule Violations (AD) [125][126][127], and Hair Sample (HS) [79]. One study [79] was found to use a method assigned to SRP and to SAP, thus it was included in both with its two assessment scores included independently in Electronic Supplementary Material Appendix S4.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Three studies employed anti-doping rule violations (ADRVs) as a method to examine doping behavior for a population of competitive athletes [125][126][127]. Examining ADRVs to determine doping prevalence offers several advantages.…”
Section: Anti-doping Rule Violationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deliberate act of doping in sport has been shown to be fueled by various different factors, appellatively summarized as a dopogenic environment by Backhouse et al, ranging from (amongst others) the enormous overall demands of the modern sporting life that might exceed an athlete's personal resources to local level factors such as the athlete's team, coach, physicians, and peers as well as sport motivation . In addition, presumably or evidently inadvertent antidoping rule violations (ADRVs) have continued to be recorded, underlining the importance of education and information of the athletes’ support personnel and health care professionals .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it suggests systemic issues in the athletes' environment. The influence of various individuals within an athlete's environment on doping risk has been studied previously, from peers in team sports (Allen et al, 2017;Aubel et al, 2019;Mallia et al, 2016), to coaches (Barnes et al, 2022), parents (Erickson et al, 2017), physicians (Backhouse & McKenna, 2011), and other athlete support personnel (Barkoukis et al, 2019, Mazanov et al, 2014. The importance of the athlete environment on doping behaviour has long been recognised in academic research (Hauw, 2013;Hauw & Mohamed, 2015;Shelley et al, 2021;Petróczi et al, 2017;Petroczi et al, 2021).…”
mentioning
confidence: 99%